Iterative model reduction of large state-space systems - Huhtanen, Marko (Zielona Góra: Uniwersytet Zielonogórski)
There exist criteria for reducing the order of a large state-space model based on the accuracy of the approximate solutions to the Lyapunov matrix equations and the Hankel operator. Iterative solution techniques for the Lyapunov equations with the Arnoldi method have been proposed in a number of papers. In this paper we derive error bounds for approximations to the solutions to the Lyapunov equations as well as for the Hankel operator that indicate how to precondition while solving these equations iteratively.
Keywords: model reduction; iterative methods; Lyapunov matrix equations; Hankel operator; preconditioning; Hankel singular values